2004
DOI: 10.1523/jneurosci.4271-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

A1 Adenosine Receptor Upregulation and Activation Attenuates Neuroinflammation and Demyelination in a Model of Multiple Sclerosis

Abstract: The neuromodulator adenosine regulates immune activation and neuronal survival through specific G-protein-coupled receptors expressed on macrophages and neurons, including the A1 adenosine receptor (A1AR). Here we show that A1AR null (A1AR Ϫ/Ϫ ) mice developed a severe progressive-relapsing form of experimental allergic encephalomyelitis (EAE) compared with their wild-type (A1AR ϩ/ϩ ) littermates. Worsened demyelination, axonal injury, and enhanced activation of microglia/macrophages were observed in A1AR Ϫ/Ϫ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
267
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(279 citation statements)
references
References 55 publications
10
267
2
Order By: Relevance
“…CD73 is a key regulator of extracellular ATP metabolism and inflammation as it shifts the balance from pro-inflammatory ATP and prothrombotic ADP to anti-inflammatory adenosine by converting AMP into adenosine. Adenosine is a known anti-inflammatory agent, which promotes endothelial integrity and has neuroprotective properties [17,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD73 is a key regulator of extracellular ATP metabolism and inflammation as it shifts the balance from pro-inflammatory ATP and prothrombotic ADP to anti-inflammatory adenosine by converting AMP into adenosine. Adenosine is a known anti-inflammatory agent, which promotes endothelial integrity and has neuroprotective properties [17,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ecto-5 0 -nucleotidase activity is upregulated in ischemic rat brains leading to increased protective purine synthesis [14]. It has been shown that A1 adenosine receptor (A1aR) knockout mice have a more severe phenotype in the murine EAE model compared with wild-type controls [24], suggesting a role for adenosine-mediated protection in EAE. A1aRs are highly expressed on microglia/macrophages and neurons in CNS and, interestingly, A1aR expression and activity on macrophage/microglial cells were shown to be diminished in MS patients compared with controls [35].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although there is a general downregulation of A 1 Rs caused by noxious stimuli, this does not mean that the ability of A 1 Rs to control neuronal damage is eliminated. In fact, some reports indicate that A 1 Rmediated neuroprotective effects may still be achieved in chronic brain noxious conditions in adult animals, such as in animal models of epilepsy [165,330,331], multiple sclerosis [332], paroxysmal dystonia [333] or 3-nitropionic acid-induced neurotoxicity [334]. It has already been discussed that the use of A 1 R agonists as neuroprotective tools in vivo may be of limited use because of their profound peripheral effects (see BAcute A 1 receptor activation increases the threshold for acute neurodegeneration^).…”
Section: Therapeutic Neuroprotective Potential Based On Adenosine In mentioning
confidence: 99%
“…Frontal brain white matter was collected at autopsy with consent from ageand sex-matched MS patients (total: n = 8; median age: 63 y; chronic progressive MS: n = 3; secondary progressive MS: n = 5) and non-MS (control) patients (total: n = 7; median age: 58 y; sepsis: n = 2; myocardial infarction: n = 2; HIV/AIDS: n = 1: cancer/leukemia n = 2) for RT-PCR analyses, as previously reported (32)(33)(34). Normal-appearing white matter (NAWM) was used from all clinical samples.…”
Section: Human Brain Tissue Samplesmentioning
confidence: 99%